Anti-Inflammatory Dipeptide, a Metabolite from Ambioba Secretion, Protects Cerebral Ischemia Injury by Blocking Apoptosis Via p-JNK/Bax Pathway - Zhang, Qian; Dai, Jinwei; Song, Zhibing; Guo, Yuchen; Deng, Shanshan; Yu, Yongsheng; Li, Tiejun; Zhang, Yuefan (Frontiers in Pharmacology, 2021)
MQ is one of the metabolites of monocyte locomotion inhibitory factor (MLIF), a thermostable pentapeptide secreted by Entamoeba histolytica. MLIF Injection had been approved as an investigational new drug for the potential neural protection in acute ischemic stroke. This study further investigated the neuroprotective effect of MQ in ischemic brain damage. Ischemia-reperfusion injury of the brain was induced in rat models by middle cerebral artery occlusion (MCAO). 2,3,5-triphenyltetra-zolium chloride (TTC) staining assay was used to measure cerebral infarction areas in rats. Laser doppler measurement instrument was used to detect rats blood flow changes in the rat model. Nissl staining and NeuN staining were utilized to observe the numbers and structures of neuron cells, and the pathological changes in the brain tissues were examined by hematoxylin-eosin (H&E) staining. Terminal deoxynucleotidyl transferase deoxyuridine triphosphate nick end labeling (TUNEL) staining was used to assess the cell apoptosis. The changes in oxidative stress indexs superoxide dismutase (SOD) and malondialdehyde (MDA) were measured in serum. Methyl Thiazolyl Tetrazolium (MTT) was used to measure the survival rates of PC12 cells. Flow cytometry instrument was assessed the apoptosis rates and the levels of reactive oxygen species (ROS). Real-Time PCR was used to evaluate the mRNA expression levels of JNK, Bax, Caspase3. Western blotting was used to analyze the changes in protein levels of p-JNK, Bax, cleaved Caspase3. We revealed that MQ improved neurobehavior, decreased cerebral infarction areas, altered blood flow volume, and the morphology of the cortex and hippocampus. On the other hand, it decreased the apoptosis of cortical neurons, the levels of MDA, and increased the levels of SOD. In vitro studies demonstrated MQ enhanced the cell survival rates and decreased the levels of ROS. Compared to the oxygen-glucose deprivation/reperfusion (OGD/R) group, the protein and mRNA expressions of p-JNK, Bax, cleaved Caspase3 was decreased significantly. These findings suggested that MQ exerts neuroprotective effect in cerebral ischemia by blocking apoptosis via p-JNK/Bax pathway.